2021
DOI: 10.1039/d0ra09878g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in nanosized metal organic frameworks for drug delivery and tumor therapy

Abstract: This review provides an overview of the recent advances in nano-MOFs for drug delivery and tumor therapy and some insight into present challenges and prospects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 163 publications
0
24
0
Order By: Relevance
“…Thus, MOFs exhibit significantly higher molecule-adsorption capabilities as compared to conventional porous materials, indicating that MOFs hold promise as innovative porous materials to replace current adsorbents. Furthermore, the high molecule-adsorption capabilities of MOFs may be advantageous for biomedical applications. In particular, MOFs have been widely studied as nanocarriers for drug delivery systems because they can be designed to exhibit controlled degradation properties in response to external stimuli such as pH change, light, and specific biomolecules by selecting appropriate metal ions and organic ligands. MOFs are particularly promising nanocarriers for delivering low-molecular-weight drugs to cells. In addition to low-molecular-weight compounds, MOFs possess protein-adsorption capabilities. Balkus and colleagues reported that CuMOF adsorbs microperoxidase (MP-11) . Chen and colleagues reported that π–π interactions between 4,4-biphenyldicarboxylates, the organic ligands of Tb-mesoMOFs, and MP-11 allow high MP-11-retention capability of Tb-mesoMOFs. , Importantly, adsorption and retention capabilities of MOFs against amyloid-β proteins strongly depend on the type of MOF; especially, MIL-53 (Al), MIL-88B (Fe), UiO-66, and MIL-101 (Cr) NDCs exhibit high adsorption and retention capabilities, , suggesting that specific interactions between amyloid-β proteins and the organic ligands of MOFs are a potential mechanism for these capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MOFs exhibit significantly higher molecule-adsorption capabilities as compared to conventional porous materials, indicating that MOFs hold promise as innovative porous materials to replace current adsorbents. Furthermore, the high molecule-adsorption capabilities of MOFs may be advantageous for biomedical applications. In particular, MOFs have been widely studied as nanocarriers for drug delivery systems because they can be designed to exhibit controlled degradation properties in response to external stimuli such as pH change, light, and specific biomolecules by selecting appropriate metal ions and organic ligands. MOFs are particularly promising nanocarriers for delivering low-molecular-weight drugs to cells. In addition to low-molecular-weight compounds, MOFs possess protein-adsorption capabilities. Balkus and colleagues reported that CuMOF adsorbs microperoxidase (MP-11) . Chen and colleagues reported that π–π interactions between 4,4-biphenyldicarboxylates, the organic ligands of Tb-mesoMOFs, and MP-11 allow high MP-11-retention capability of Tb-mesoMOFs. , Importantly, adsorption and retention capabilities of MOFs against amyloid-β proteins strongly depend on the type of MOF; especially, MIL-53 (Al), MIL-88B (Fe), UiO-66, and MIL-101 (Cr) NDCs exhibit high adsorption and retention capabilities, , suggesting that specific interactions between amyloid-β proteins and the organic ligands of MOFs are a potential mechanism for these capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Metal complexes offer the prospect of novel drugs with new mechanisms of action that can combat resistance to current clinical drugs, especially in the treatment of cancer and microbial infections. 10,12,[41][42][43][44][45][46] Improvements in the design of metallodrugs require consideration not only of the role of the metal and its oxidation state, but also that of the ligands, both monodentate and chelating ligands. Investigation of the redox and ligand exchange chemistry of metallodrugs inside cells is a major challenge, but an important step towards optimising structure-activity relationships for both efficacy and unwanted side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…As of May 2017, the U.S. Food and Drug Administration (FDA) has received more than 80 applications for drug products containing nanocrystals [177]. Since the nanocrystalline medicine does not need a carrier, it has the benefits of high drug loading, not being restricted by the encapsulation rate, and a wide range of drug dosage adjustments.…”
Section: Pure Nanodrugsmentioning
confidence: 99%